Mathematical Modelling and Simulation Strategies for Controlling Damage to Forest Resources Due to Illegal Logging - Naben, Irene R; Bano, Elinora N; Blegur, Fried M. A. (Jurnal Varian, 2024)
Forests are one of the natural resources that provide many benefits for the welfare of living things.The dense population causes people to depend more on forest resources. One of them is illegal logging.Various strategies to control forest damage due to illegal logging have been carried out, namely by directhandling to improve damaged conditions while preventing the recurrence of forest damage. The purposeof this research is to build a mathematical model of forest resource damage control strategies due toillegal logging, determine assumptions, formulate the model, and conduct analysis and problem solvingincluding: determining the equilibrium point, determining the stability analysis of the equilibrium point,and conducting numerical simulations of the equilibrium point. The last step is to interpret the results ofthe analysis obtained and make conclusions. Based on the research and simulation results of the model,it can be concluded that taking into account the variable of forest resource damage control strategydue to illegal logging, the result shows that if the density of forest resources has been affected by thedisturbance of population density around the forest, it is necessary to have a forest resource damagecontrol strategy in order to compensate for the people around the forest who do a lot of illegal logging.In order to maintain the forest so that the forest does not quickly become extinct and can overcomedrought, prevent flooding, maintain groundwater quality, protect animals, reduce air pollution, climatecontrol, reduce dust particles, prevent the greenhouse effect, supply natural fertilizers, prevent erosion,and maintain springs.